Portfolio: Hybrid Form, Bonny Cassidy, 2019 - Bonny Cassidy (2019)
Background - This folio is a development of form that I began in ‘grounds’ (2016) and ‘Hexham’ (2017), which applied lyric essay as a form to explore themes of colonisation. In this folio, published in 2019, I have sought to push formal experimentation further as a deepening of that theme. It is influenced by the lyric essays of Claudia Rankine and Natalie Harkin, and the prose poems of Alison Whittaker, which interrogate US and Australian black histories through a breakdown and reconstruction of creative form. Contribution - My recent hybridising of poetic and prose forms interrogates whiteness in Australia. It allows me to inhabit this theme through first-person voice, while deploying citation of broader contexts and sources. ‘Monument’ concerns public memorials in the process of Reconciliation, drawing on First Nations commentary as well as non-Indigenous voices and my own feelings about the materiality of a monument to colonial violence. ‘Cultural studs’ is a micro-essay on cultural gatekeeping, and the ambiguity of the form compresses narrative, memoir and criticism into a poetic fragment. ‘Trespass’ takes the use of memoir further, observing how inherited colonial violence ripples through everyday bodies. The prose allowed me to push nonfiction elements into fictive amplifications for thematic impact. Significance - ‘Monument’ was published online in the ‘Stories’ segment of Melbourne Knowledge Week 2019, which in 2018 attracted over 200 readers. It was performed for an open public audience during MKW as ‘A chorus of voices’: https://mkw.melbourne.vic.gov.au/events/chorus-of-voices/ ‘Cultural studs’ was published in the annual Spineless Wonders anthology celebrating micro-prose forms, and was a finalist in the national joanne burns Microlit Prize. ‘Trespass’ was commissioned for issue 9.1 of the Australian Poetry Journal, guest edited by John Kinsella under the theme of ‘resist!’.